AN ANTHOLOGY OF THE DISTINGUISHED ACHIEVEMENTS IN SCIENCE AND TECHNIQUE. PART 39: NOBEL PRIZE LAUREATES IN PHYSICS FOR 2011-2015 - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. Implementation of brief analytical review of the distinguished scientific achievements of the world scientists-physicists, awarded the Nobel Prize on physics for the period 2011-2015. Methodology. Scientific methods of collection, analysis and analytical treatment of scientific and technical information of world level in area of astrophysics, physics of elementary particles, physics of high energies, of modern theoretical and experimental physics. Results. The brief analytical review of the scientific openings and distinguished achievements of scientists-physicists is resulted in area of modern physical and technical problems which were marked the Nobel Prizes on physics for the period 2011-2015. Originality. Systematization is executed with exposition in the short concentrated form of the known scientific and technical materials, devoted opening of acceleration of expansion of Universe, creation of breach technologies of manipulation the quantum systems, theoretical discovery of mechanism of origin of mass of under-atomic particles, invention of effective power sources of light − blue light-emitting diodes and opening of neutrino oscillations. Practical value. Popularization and deepening of scientific and technical knowledges for students, engineers and technical specialists and research workers in area of modern theoretical and experimental physics, extending their scientific range of interests and cooperation in further development of scientific and technical progress in human society.